(r,p)-absolutely summing operators on the space C (T,X) and applications - Dumitru Popa (Abstract and Applied Analysis)
We give necessary and sufficient conditions for an operator on the space C (T,X) to be (r,p)-absolutely summing. Also we prove that the injective tensor product of an integral operator and an (r,p)-absolutely summing operator is an (r,p)-absolutely summing operator.